The architectural and cultural reception of the Temple of Apollo at Bassai and its frieze - O'Neill, Suzanne (Trinity College Dublin. Long Room Hub, 2008)
This project is an analysis of how this Classical Greek temple and important UNESCO world heritage site, situated in ancient Arcadia, has impacted on art, architecture and academia, creating new narratives within specific social, politicial and religious contexts.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Classics; Ancient Greece; Architecture -- Classical; Peloponnesian War -- Representation in art; Temple of Apollo